A Review of 11 Years of Stenotrophomonas maltophilia Blood Isolates at a Tertiary Care Institute in Canada - Prenilla Naidu; Stephanie Smith (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Stenotrophomonas maltophilia has emerged as a significant nosocomial pathogen with increasing resistance to trimethoprim/sulphamethoxazole (TMP/SMX), the current drug of choice for treatment.